The Effect of Nutrition Training on The Mothers Knowledge Whose Children Are Picky Eaters - Reni Sofiyatin; Lalu Khairul Abdi (Jurnal Kesehatan Prima, 2022)
Background: Preschool age (4-6 years) children experience several eating problems, one of which is picky eating. One of the factors that influence picky eater behavior in children is the practice of parenting practices adopted by parents. A good mother's knowledge the expected to shape attitudes and behaviors that can shape children's excellent and healthy eating habits. Objectives: The study of the effect of nutrition training on mothers on the knowledge of mothers whose children experience picky eating. Method: Quasi-experimental research design with pre-post only group design, statistical analysis using Paired T-Test. Results: The level of knowledge of mothers before training with fewer categories was 19 people (63%); after training, the level of knowledge was 19 people (64%) and good one person (3%). Training effects increase the knowledge of mothers whose children experience picky eating (p = 0.006 <α = 0.05). Before training, the average knowledge score was 53 points, increasing to 61.3 points after training with an average increase of 8.3 points. Conclusion: Training increases the knowledge of mothers whose children experience picky eating (p = 0.006 <α = 0.05).